Caracterização, avaliação das propriedades físicomecânicas e atividade antifúngica após escovação de resinas acrílicas termopolimerizadas incorporadas com nitrato de cério - Campos, Débora e Silva (2022)
Background: The colonization of polymethyl methacrylate (PMMA) by microorganisms favors the development of denture stomatitis. Cerium nitrate (CN) has been shown to be an effective antifungal when incorporated into PMMA, with favorable physicochemical and thermal properties. However, there is a need to continue studies to evaluate the other properties. Purpose: To characterize and evaluate the physical-mechanical properties and antifungal activity after brushing a thermopolymerized acrylic resin modified with the incorporation of different percentages by mass (0.25%, 0.5% and 1%) of CN. Materials and methods: Five groups of PMMA samples were made (CG1-PMMA; CG2-PMMA+alcohol; CN 0.25%; CN-0.5% and CN-1%). Structural characterization was performed using FTIR spectroscopy, and contact angles, porosity, Vickers hardness, flexural strength, abrasion resistance (mass variation and surface roughness) and antifungal activity after brushing were evaluated. Results: FTIR spectroscopy confirmed the presence of CN in the samples through characteristic peaks. The experimental groups containing NC did not differ in relation to CG1 in terms of contact angle, porosity and roughness variation in the analysis of abrasion resistance. The mass variation showed a reduction in the CG1 and CN-1% groups, and an increase in the CG2, CN-0.25% and CN-0.5% groups. After brushing, there was a reduction in the adhesion of fungal biofilm in the samples of CN-0.25% and CN-0.5%. For flexural strength, only CN-0.5% did not show statistical differences from CG1. The evaluation of Vickers hardness showed a reduction in the experimental groups. Conclusion: The incorporations of CN 0.25% and CN-0.5% proved to be the most promising, with a reduction in the formation of fungal biofilm even after irregularities from brushing, without changes in the porosity angle, contact angle and roughness variation. Despite the reduction in hardness, the flexural strength showed values above the acceptable limit.